The role of the teacher-student relationship in the innovation of education: Interdisciplinary review of the issue - B.G. Kálmán; N. Poyda-Nosyk (Mukachevo State University, 2023)
Many contemporary authors addressed digital and online education, competencies, and lifelong learning. However, less is said about the importance of interpersonal relationships, even though they are essential for preserving the sustainability of education. The research aims to examine the field of human relations. To achieve this goal, the theory of organisational and social psychology was used. Relations can only be implemented through interpersonal dialogue. From an environmental perspective, both subjective and objective factors were determined to define the strength of the relationship. It was concluded that the teacher's personality is the key to success at all levels of education. It is justified that the result of curricula's central regulation is that the education of tomorrow's professionals is directed by today's professionals, who often have an interest in providing what is needed now rather than what may be needed in the future. It is proved that it is not enough for students to be aware of the academic mission, nor for the university to be a kind of training site for the labour market. From a socio-psychological perspective, it was disclosed that teaching quality mattered most, but subject to the theory of organisational psychology. The introduced materials can be utilized by universities to work on the nature of graduates' preparation through the advancement of their character. Considering various approaches to the organization of education participants' activities and characteristics of their self-development, the model for the formation of the value system of future teachers will make it possible to provide conditions for the individualization of training paths.